How the Internet of Things Changes Everything: The next stage of the digital revolution - Carruthers, Kate (Journal of Telecommunications and the Digital Economy, 2020)
In many ways the Internet of Things will change everything, as devices and software mesh and become part of the connected fabric of the Internet. This article explores the context and potential offered by the growth of the Internet of Things (IoT). It provides an overview of this next phase of the digital revolution that is underpinned by the growth of the social web, web 2.0, and the convergence of technologies such as mobile and ubiquitous broadband. This article also attempts to provide some insight into the potential value of the Internet of Things market in the future. The opportunities offered by the Internet of Things also raise serious questions about privacy and security in a connected world. As Umair Haque noted recently: “At some point, we should all question the value of an internet that objectifies you, tracks you, and polices you...without your consent.” (Haque 2014)